VENTILASI, KEPADATAN HUNIAN DAN KEJADIAN ISPA PADA BALITA DI PUSKESMAS PASAR IKAN KOTA BENGKULU - Suryani Suryani; Buyung Keraman; Sartika Sartika (Jurnal Sains Kesehatan, 2017)
Incidence of Acute Respiratory Infection (ARI) can affect mortality in infants. This study aimed to study the relationship between ventilation and occupancy density with incidence of ARI among Children under five in Pasar Ikan Public Healt Center Bengkulu. The type of this research was Analytical Survey with cross sectional design. The population in this study was all mothers who had children aged 6-24 months, who visited Pasar Ikan Public Health Center Bengkulu. Sample used in this research was mother who had children aged 6-24 month who visited to Pasar Ikan Public Health Center Bengkulu as much as 52 mothers. In this study the sample used was Accidental Sampling. The data used were primary data and secondary data. The analysis was performed by using univariate analysis and bivariate analysis with Chi-Square statistical test (χ2). To know the closeness of the relationship was used statistical test Contingency Coefficient (C). The results showed that of 52 mothers, 37 mothers (71.2%) had inadequate home ventilation, 25 mothers (55.9%) who had unsuitable occupancy density conditions, 38 mothers (73.1% ) had children who had incidence of ARI, there was a relationship between ventilation with incidence of ARI with moderate relationship category, and there was a relationship between occupancy density and incidence of ARI with medium relations category. Keywords: ARI incidence, occupancy density, ventilation